The Effectiveness of Cabbage Leaf Compress and the Education of Lactation Management in Reducing Breast Engorgement in Postpartum - Napisah, Pipih; Widiasih, Restuning; Maryati, Ida; Hermayanti, Yanti; Natasya, Windy (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Breast engorgement is a common problem of breastfeeding. The combination of nursing interventions is expected to prevent and reduce breast engorgement promptly. AIM: This study aims to determine the effectiveness of cabbage leaf compress and education on lactation management for reducing breast engorgement in postpartum. METHODS: This study was a quasi-experimental study with a non-equivalent control group design. The sample was 60 postpartum women (n = 30 the intervention group and n = 30 the control group) selected by purposive sampling. The instrument was the Breast Engorgement Scale. The intervention included giving compress on women’s breast using the cabbage leaf and educating them about lactation management, while the control group was given treatment according to hospital standard procedures. The study was conducted in a national referral hospital for West Java Province areas, Indonesia. Data were analyzed using the Wilcoxon sign-rank test and the effectiveness of intervention tested using the NGain score test. RESULTS: There was a difference in breast engorgement scale before intervention with median value ± min max (3.00 ± 2-6) and after median ± min max (2.00 ± 1-2), while in the control group the breast engorgement scale before treatment showed the median was ± min-max (2.00 ± 2-5) and after treatment, was ± min-max (2.00 ± 1-5). The effectiveness of intervention was 77.56%. CONCLUSIONS: The combination interventions of cabbage leaf compress and lactation management education were effective in reducing the breast engorgement in postpartum. This intervention can be used as an alternative intervention to solve the breast engorgement problem in postpartum women, especially for a developing country like Indonesia, because the cabbage leaf is cheap and easy to get in the traditional market. Further research is expected to conduct research on a qualitative design to understand women’s experience after interventions and the possibility to apply this intervention at home.